Estudio y análisis para mejorar la productividad en el área de granallado metálico de planchas y perfiles de acero en la empresa SEDEMI S.S.C. - Lliquin Mosquera, Luis Francisco (2018)
The present research project deals with analysis in the metal granted area of plates and steel profiles that generates low productivity in the process due to dead times, recurious distance from the material, badrubution of the plant, through the compilation of information of the process, for later pose a proposal for improvement. The methodology that I use for the elaboration of the work is inductive and adapt a field modality by applying bibliographic techniques and tools such as observation to assess the productive system of the protruding process in the company SEDEMI S.C.C. Next, a proposal of improvement is proposed by designating a new distribution of plant and standardization of times in the process and improve productivity with the analysis and tools of slender manufacturing. With the proposal of improved presented, it is possible to correct the errors and the stage of process is streamlined allowing workers to make their own ease of their tasks with a self-assessment control of 5” S”, it was achieved to reduce from 450 to 371,53 optimizing 78,48 process of minutes allowing to increase the daily production of 3,4 to 4 tons.